Audit of the Financial Audit Agency on the Procurement of Goods and Services Reviewed from the Corruption Eradication Commission (Case Study of Land Acquisition Owned by the Sumber Waras Health Foundation by the Regional Government of DKI Jakarta Province - Fatimah, Siti; Sulaiman, Abdullah; Hidayati, Hidayati (Green Publisher Indonesia, 2024)
The report on the results of the investigation by the Jakarta Provincial Government's Financial Audit Agency in 2014 explained that there were irregularities in the purchase of 36,410 square meters of land belonging to the Sumber Waras Health Foundation by the Jakarta Provincial Government. The purpose of this study is to understand the indications of state financial irregularities or according to the rules when reviewed from the Corruption Eradication Commission. The method uses a normative juridical approach, using literature or secondary data as the basis for research, and is carried out by looking for regulations and literature related to the problem being studied. The results explained that the Financial Audit Agency claimed that the purchase of land for the Sumber Waras Health Foundation was found to have the potential to harm the state reaching Rp191 billion, which was reported during a hearing at Commission three of the House of Representatives of the Republic of Indonesia with the Corruption Eradication Commission on June 14, 2016. Based on Law 30 of 2002 concerning the Corruption Eradication Commission which has conducted an investigation, two crucial numbers are explained, including: first, the investigators of the Corruption Eradication Commission stated that they did not find any unlawful acts in the purchase of land for the Sumber Waras Health Foundation; Second, the Corruption Eradication Commission invited experts, including the Indonesian Appraiser Professional Association. According to the results reported by the Financial Audit Agency regarding the finances of the DKI Jakarta Provincial Government in 2014 and the investigation from the Audit of the Financial Audit Agency, there were six irregularities including planning, budgeting, team formation, procurement, price formation, and delivery of results. As a result, the state's financial losses amounted to Rp191 billion.